TRANSFORMATIONAL LEADERSHIP AND ITS IMPACT ON EMPLOYEE MOTIVATION AND PRODUCTIVITY - Ainal Ikram; Ervin Nora Susanti; Firdaus Hamta (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Transformational leadership has become one of the most influential leadership approaches in modern organizational management due to its ability to enhance employee motivation and productivity. This study employs a narrative literature review approach to examine the relationship between transformational leadership, employee motivation, and organizational productivity. The findings indicate that transformational leadership positively influences employee engagement, job satisfaction, creativity, and organizational commitment through inspirational motivation, intellectual stimulation, individualized consideration, and idealized influence. Employees led by transformational leaders are more likely to demonstrate higher productivity, innovation, and collaborative behavior within the workplace. The study also reveals that effective communication and supportive organizational culture strengthen the impact of transformational leadership on employee performance. Furthermore, transformational leadership contributes to organizational adaptability and long-term sustainability in dynamic business environments. This study provides theoretical and practical insights for organizations seeking to improve employee performance through people-oriented leadership strategies and highlights the importance of leadership development in achieving organizational success.